Human rights, sexual orientation and gender identity in the Commonwealth : struggles for decriminalisation and change - Lennox, Corinne; Waites, Matthew (Human Rights Consortium, Institute of Commonwealth Studies, School of Advanced Study, University of London, 2013)
Human Rights, Sexual Orientation and Gender Identity in The Commonwealth: Struggles for Decriminalisation and Change challenges these developments as the first book to focus on experiences of lesbian, gay, bisexual, transgender and intersex (LGBTI) and all non-heterosexual people in the Commonwealth. The volume offers the most internationally extensive analysis to date of the global struggle for decriminalisation of same-sex sexual behaviour and relationships.